Electrochemical supercapacitive performance study of spray pyrolyzed cobalt oxide film. (2021) - Jadhav, C.H.; Pisal, K.B.; Chavan, A.R.; Patil, S.M.; Patil, P.B.; Pagare, P.K.
Abstract: The cobalt oxide film has been synthesized on the indium doped tin oxide (ITO) substrate using spray pyrolysis method at 350 °C temperature. The structural and morphological properties of prepared cobalt oxide film was characterized by X-ray diffraction (XRD), scanning electron microscopic (SEM) systems correspondingly. The XRD analysis show polycrystalline nature of cobalt oxide film. From the UV–Visible absorption spectra, band gap property of cobalt oxide film has been studied. The electrochemical supercapacitive performance of cobalt oxide film is evaluated by cyclic voltammetry technique. The cobalt oxide film showed maximum specific capacitance of 185 F/g in 1.0 M aqueous KOH electrolyte at scan rate 10 mV/s.